2021
DOI: 10.4049/jimmunol.2001167
|View full text |Cite
|
Sign up to set email alerts
|

Neddylation Alleviates Methicillin-Resistant Staphylococcus aureus Infection by Inducing Macrophage Reactive Oxygen Species Production

Abstract: Neddylation, a posttranslational modification in which NEDD8 is covalently attached to target proteins, has emerged as an endogenous regulator of innate immunity. However, the role of neddylation in methicillin-resistant Staphylococcus aureus (MRSA) infection remains unknown. In this study, we found that neddylation was activated after MRSA infection in vivo and in vitro. Inhibition of neddylation with MLN4924 promoted injury of liver and kidneys in C57BL/6 mice with MRSA bloodstream infection and increased mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Further gene set enrichment analysis (GSEA) indicated a significant inhibition of multiple biological processes, including macrophage activation, innate immune response, adaptive immune response, and Gram-positive bacterial defense response (Figure 1 F). Given that ROS generation is critical to effective antimicrobial activity of activated macrophages 30 , 31 , we investigated the dynamic ROS changes in primary murine bone marrow-derived macrophages (BMDMs) following S. aureus infection. Results showed that the level of ROS was significantly increased at 6 hours post-infection, followed by a marked decrease at 12 and 24 hours (Figure 1 G and 1 H).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further gene set enrichment analysis (GSEA) indicated a significant inhibition of multiple biological processes, including macrophage activation, innate immune response, adaptive immune response, and Gram-positive bacterial defense response (Figure 1 F). Given that ROS generation is critical to effective antimicrobial activity of activated macrophages 30 , 31 , we investigated the dynamic ROS changes in primary murine bone marrow-derived macrophages (BMDMs) following S. aureus infection. Results showed that the level of ROS was significantly increased at 6 hours post-infection, followed by a marked decrease at 12 and 24 hours (Figure 1 G and 1 H).…”
Section: Resultsmentioning
confidence: 99%
“…It is known that the antibacterial activity of macrophages is closely related to the ROS generation 30 , 31 . To evaluate the role of SLC7A11 in regulating intracellular ROS levels in response to S. aureus infection, we used fluorescence probe DCFH-DA for labeling ROS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Murine MH‐S cells (CRL‐2019) were purchased from the American Type Culture Collection (Manassas, VA, USA), and acute monocytic leukaemia THP‐1 cells (TCHu57) were purchased from the Type Culture Collection of the Chinese Academy of Sciences (Shanghai, China). Mouse primary peritoneal macrophages (MP‐Mφ) were isolated from mice as previously described (Xiu et al., 2021 ) and the isolation service of human primary CD14 + monocytes (HP‐Mφ) from peripheral blood mononuclear cells was provided by Milestone Biotechnology (Hangzhou, China). MH‐S and THP‐1 cells, as well as MP‐Mφ and HP‐Mφ, were cultured in RPMI‐1640 (Basalmedia) supplemented with 10% FBS (Thermo Fisher Scientific) and 1% penicillin/streptomycin, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Except for affecting inflammatory responses, MLN4924 also promotes polarization towards M2 macrophages ( Asare et al, 2017 ). The neddylation pathway was found to be activated during methicillin-resistant Staphylococcus aureus (MRSA) infection, providing protection through the NEDD8-Cullin3-Nrf2-ROS axis and increased reactive oxygen species (ROS) in mouse peritoneal macrophages ( Xiu et al, 2021 ). Moreover, neddylation inhibition was proved to decrease macrophage tumor infiltration through chemotactic cytokine ligand 2 (CCL2) reduction, thus modulates the tumor microenvironment and could be a potent cancer therapy ( Zhou et al, 2019 ; Meerang et al, 2020 ).…”
Section: Neddylation and Innate Immune Cellsmentioning
confidence: 99%